2010
DOI: 10.1111/j.1463-5224.2010.00812.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular disease in the guinea pig (Cavia porcellus): a survey of 1000 animals

Abstract: This study shows a high proportion of eyes with some degree of abnormality in animals otherwise considered healthy. Information on diseases of the guinea pig eye is important given the use of the species as a laboratory rodent and also the number kept as pets and show animals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 22 publications
3
37
3
2
Order By: Relevance
“…Williams and Sullivan [33] found that an excess of vitamin C can cause ocular abnormalities in guinea pigs, but the risks associated with hypovitaminosis C appear to outweigh any adverse effects associated with excessive supplementation. However, a high percentage of owners supplementing their animals with vitamin C was also seen in a similar study with the authors stating that the management of dietary uptake of vitamin C in guinea pigs should always be discussed [21].…”
Section: Discussionmentioning
confidence: 99%
“…Williams and Sullivan [33] found that an excess of vitamin C can cause ocular abnormalities in guinea pigs, but the risks associated with hypovitaminosis C appear to outweigh any adverse effects associated with excessive supplementation. However, a high percentage of owners supplementing their animals with vitamin C was also seen in a similar study with the authors stating that the management of dietary uptake of vitamin C in guinea pigs should always be discussed [21].…”
Section: Discussionmentioning
confidence: 99%
“…The guinea pig retina is avascular (De Schaepdrijver et al, 1989), which is a substantial difference to the human. Spontaneous glaucoma has not been reported for guinea pigs (Williams and Sullivan, 2010) and it is still uncertain whether or not animals of this species would develop glaucomatous damage after experimental elevation of IOP. A promising novel animal model for glaucoma research may be the tree shrew (family Tupaiidae), a non-rodent, primate-like species (Cao et al, 2003) that has been widely used in myopia research.…”
Section: Animal Models Of Glaucomamentioning
confidence: 99%
“…In that study, absolute values were also not reported, IOP data being described only in terms of statistical significance of differences between treated and fellow control eyes for given conditions. Two other studies involving guinea pigs made use of applanation tonometers (Coster et al, 2008; Williams and Sullivan, 2010). In the first study using a Tonopen applanation tonometer to measure 100 normal guinea pigs (age unknown), an average IOP of 16.5 ± 3.2 mmHg was reported (Williams and Sullivan, 2010), similar to the mean IOP of our 2 weeks-old animals (17.6 ± 2.6 mmHg), but significantly lower than our mean value for older animals (22.7 ± 2.3 mmHg).…”
Section: Discussionmentioning
confidence: 99%